A facile one-step electrochemical preparation of graphene–Pd nanocomposite as a catalyst for hydrogen evolution reaction - Fatemeh Norouz-Sarvestani; Seyyed Mehdi Khoshfetrat (Nanochemistry Research)
This study describes a one-step, facile, simple, and effective electrochemical method for the codeposition of graphene oxide (GO) and Pd nanoparticles (NPs) onto a carbon paste electrode (CPE). The obtained nanocomposite was characterized using scanning electron microscopy, cyclic voltammetry, and chronocoulometry techniques, which confirmed the high dispersion and stability of PdNPs supported on the graphene. This procedure does not require the use of a reducing agent or surfactant, making the preparation process very clean. This catalyst showed superior electrocatalytic activity and stability toward hydrogen evolution reaction (HER) when compared to either PdNPs or graphene alone, indicating the synergistic effect of graphene and PdNPs. The Tafel slopes of HER on both bare and modified CPE were determined to be 97 and 146 mV dec-1, respectively. In addition, the kinetic parameters showed that the Volmer step must control the HER. This study suggests an effective and controllable method for preparing graphene–metal NPs with high electrocatalytic activity.